Metabotropic GPCRs: TGR5 and P2Y Receptors in Health and Diseases - Rajagopal, Senthilkumar (Springer Singapore, 2018)
This book will provide current understandings about two ubiquitously expressed metabotropic GPCRs, G-coupled purinoreceptor type 2 (P2Y) and Takeda G-protein-coupled bile acid receptor 5 (TGR5). G protein coupled receptors (GPCRs) are the largest family of proteins implicated in majority of cellular responses. The two receptor sub-families play a central role in many physiological functions as well as in many pathological conditions. This book offers up-to-date information on the physiological functions, signaling pathways and regulatory mechanisms of P2Y and TGR5 receptors. In addition, this book provides a comprehensive overview about the abnormalities of P2Y/TGR5 receptors and their contribution in the development and progression of pathological conditions. It also covers the currently available natural, chemical and pharmacological agents targeting these two receptor families and their therapeutic implications in P2Y and TGR5 associated disorders. This book is a valuable source for beginners and researchers to follow the rapidly progressing field of these two GPCR subfamily members.